The narrative, descriptive and argumentative forms of expression in terms of the systemic-functional analysis of discourse - Wolańska, Ewa; Wolański, Adam (Papers in Linguistics, 2019)
The article contains a deconstructive analysis of three relatively common forms of expression: narrative, description and argumentation. This analysis refers to the systemic-functional analysis of discourse, which emphasizes the situational, contextual and cultural aspects of language use. The results of the research may prove useful in the speech therapy theory and practice, dealing with various types of discourses in the norm and pathology.